Development of NIRS method for quality control of drug combination artesunate-azithromycin for the treatment of severe malaria - Boyer, C; Gaudin, K; Kauss, T; Gaubert, A; Boudis, A; Verschelden, J; Franc, M; Roussille, J; Boucher, J; Olliaro, P; White, N; Millet, P; et al. (Elsevier, 2012)
Near infrared spectroscopy (NIRS) methods were developed for the determination of analytical content of an antimalarial-antibiotic (artesunate and azithromycin) co-formulation in hard gelatin capsule (HGC). The NIRS consists of pre-processing treatment of spectra (raw spectra and first-derivation of two spectral zones), a unique principal component analysis model to ensure the specificity and then two partial least-squares regression models for the determination content of each active pharmaceutical ingredient. The NIRS methods were developed and validated with no reference method, since the manufacturing process of HGC is basically mixed excipients with active pharmaceutical ingredients. The accuracy profiles showed β-expectation tolerance limits within the acceptance limits (±5%). The analytical control approach performed by reversed phase (HPLC) required two different methods involving two different preparation and chromatographic methods. NIRS offers advantages in terms of lower costs of equipment and procedures, time saving, environmentally friendly. © 2012 Elsevier B.V.